Delineating genotype × environment interaction for horticultural traits in tomato using GGE and AMMI biplot analysis - Jagesh Kumar Tiwari; Nagendra Rai; Manish Kumar Singh; Yerasu Suresh Reddy; Rajesh Kumar (Scientific Reports)
Abstract The aim of this study was to identify stable tomato hybrids for cultivation in India. The genotype-by-environment (G × E) interaction analysis was performed using GGE and AMMI biplots. Fifteen hybrids including two checks were grown in nine environments during winter, summer, and rainy seasons from 2021 to 2024 at Varanasi. G × E interaction was investigated for days to first harvesting, average fruit weight, pericarp thickness, total soluble solids (TSS), yield, and resistance to tomato leaf curl virus disease (ToLCD). The GGE biplot analysis identified stable and superior hybrids as well as ideal environments, based on mean vs. stability, which-won-where, discriminativeness vs. representativeness, genotype by trait (GT), genotype by yield × trait (GYT), and multi-trait genotype-ideotype distance index (MGIDI). As a result, we identified stable hybrids such as VRTH-16-4 (G2) and VRTH-16-3 (G1) for yield; VRTH-16-70 (G5) and VRTH-19-18 (G11) for days to first harvesting; VRTH-16-5 (G3) and VRTH-16-8 (G4) for fruit weight; VRTH-16-8 (G4) and VRTH-16-5 (G3) for pericarp thickness; VRTH-16-75 (G6) and VRTH-18-26 (G8) for TSS; and VRTH-16-5 (G3) and VRTH-16-70 (G5) for ToLCD resistance. Overall, this study highlights that tomato hybrids VRTH-16-4, VRTH-16-90, and VRTH-18-46 have potential for cultivation during heat and cool weather conditions.